2021
DOI: 10.1371/journal.pone.0256288
|View full text |Cite
|
Sign up to set email alerts
|

Tackling exclusion: A pilot mixed method quasi-experimental identity capital intervention for young people exiting homelessness

Abstract: Background Longitudinal studies examining the life trajectories of young people after they have exited homelessness have identified concerns with persistent social and economic exclusion, struggles to shake off identities of homelessness, and housing instability. This pilot study sought to explore the feasibility of improving socioeconomic inclusion outcomes by bolstering identity capital (sense of purpose and control, self-efficacy and self-esteem) among young people who had experienced homelessness. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We selected community integration (psychological and physical) and self-esteem-proxy indicators of socioeconomic inclusion-as primary outcomes based on our frontline clinical and research experience with this population. 8,10,28,29 Community integration was measured with the Community Integration Scale, 19,20 with a score range of 1 to 7 for the physical component and 4 to 20 for the psychological component; higher scores indicate higher integration (Table 1). [18][19][20][21][22][23][24][25][26] Self-esteem was…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected community integration (psychological and physical) and self-esteem-proxy indicators of socioeconomic inclusion-as primary outcomes based on our frontline clinical and research experience with this population. 8,10,28,29 Community integration was measured with the Community Integration Scale, 19,20 with a score range of 1 to 7 for the physical component and 4 to 20 for the psychological component; higher scores indicate higher integration (Table 1). [18][19][20][21][22][23][24][25][26] Self-esteem was…”
Section: Discussionmentioning
confidence: 99%
“…The annual cost of housing Toronto participants was roughly 6.5 times less expensive than the annual cost of staying in a shelter. Moreover, the sense of personal agency and control that comes from having choice is fundamental to recovery-oriented care, and emerging evidence signals that agency and control could be important mediating factors in outcomes related to mental well-being and housing stability for youths who have experienced homelessness . An unexpected finding was the substantial number of young people who chose to move back home and provide the rent subsidies to their parent(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that YEH also experience high levels of mental distress, including anxiety, depression, and suicidal ideation, likely the result of trauma and adverse childhood experiences [ 7 ]. They face multiple barriers to social inclusion, including maintaining employment and remaining in school, and often have limited social networks and supports [ 8 ]. The experience of homelessness, particularly when prolonged, can be traumatic in itself, and can lead to worsened mental health, substance use, and exposure to exploitation and victimization [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%